Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1590/s0073-47212009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Influência da ação antrópica sobre a fauna de macroinvertebrados aquáticos em riachos de uma região de cerrado do sudoeste do Estado de São Paulo

Abstract: ABSTRACT. Anthropic action influence on aquatic macroinvertebrates in streams from a cerrado region of Southwestern of the State of São Paulo, Brazil. The richness and spatial distribution of aquatic macroinvertebrates were studied in streams from a cerrado region, Assis, State of São Paulo, with the purpose of verifying the effect of the anthropic action on the fauna. The collections took place at the headwaters of the Ribeirão Água do Cervo (the main water supplier of the city of Assis). Nine collection stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
1
9
0
4
Order By: Relevance
“…(Kalkman et al, 2008;Juen et al, 2014). Moreover, studies have reported the dominance of Libellulidae immature in streams near pastures, with degraded riparian forests or in silted streams (Cortezzi et al, 2009;Dalzochio et al, 2011a). Our results confirm this pattern since most of the stretches sampled in both streams are shallow and the surroundings consist mainly of grass pastures and sparse fragments of riparian vegetation.…”
Section: Discussionsupporting
confidence: 88%
“…(Kalkman et al, 2008;Juen et al, 2014). Moreover, studies have reported the dominance of Libellulidae immature in streams near pastures, with degraded riparian forests or in silted streams (Cortezzi et al, 2009;Dalzochio et al, 2011a). Our results confirm this pattern since most of the stretches sampled in both streams are shallow and the surroundings consist mainly of grass pastures and sparse fragments of riparian vegetation.…”
Section: Discussionsupporting
confidence: 88%
“…The changes in species composition occurred mainly between preserved streams and those in intermediate and degraded stages condition, representing responses that are common in aquatic communities exposed to gradients of habitat degradation (Kikuchi & Uieda, 1998;Cortezzi et al, 2009;Johnson & Hering, 2009). Changes in the species composition observed in this study were also accompanied by functional composition changes in communities, represented by the dominance of tolerant and opportunist fishes, in detriment to the diminution/ elimination of more sensitive and specialized species along the degradation gradient of riparian zone.…”
Section: Discussionmentioning
confidence: 52%
“…The study of the ecological integrity of ecosystems may use the response of the organisms to changes in the environment where they live, which can be of anthropogenic or natural origin (Buss et al 2003). This use of biological variables in monitoring programs enables a wide and integrated characterization of the effects of various disorders, providing data on the environmental conditions over time (Iliopoulou-Georgudaki et al 2003, Cortezzi et al 2009. Among the aquatic communities, invertebrates are good indicators of environmental conditions (Callisto et al 2001), and so are widely used in environmental impact assessments and biological monitoring Callisto 2003, CETESB 2013).…”
Section: Introductionmentioning
confidence: 99%